Neoadjuvant chemotherapy with paclitaxel/carboplatin/bevacizumab in advanced vulvar cancer: Time to rethink standard of care? - Madison R. Klavans; Sarah H. Erickson; Susan C. Modesitt (Elsevier, 2020)
Vulvar cancer remains a rare entity and treatment options for advanced disease are limited. This case report highlights the excellent response of two patients with FIGO Stage IV vulvar cancer treated with neoadjuvant paclitaxel/carboplatin/bevacizumab chemotherapy. While definitive conclusions are impossible, neoadjuvant chemotherapy may ultimately prove to be a better initial treatment option for locally advanced disease in terms of quality of life and response compared to the traditional chemoradiation regimens.